Jewell, Women In Dark Age And Early Medieval Europe, C. 500-1200 - Dickens, Andrea Janelle (Teaching History: A Journal of Methods, 2008)
Jewell has presented us with a fine example of her scholarship in Women in Dark Age and Early Medieval Europe, c. 500-1200. The book covers the historiographic evidence on the status of women and the minutiae of their lives based upon settlement archaeology, ethnographic data, administrative records such as wills and land grants, as well as the infrequent documentary evidence of the period. Her book adds considerably to the field by the wide geographic scope of its coverage as well as by the combination of forms of evidence she incorporates. In the Introduction, Jewell provides the reader with a summary of other research on the topic and its relative strengths and weaknesses.